Batik-Based Interior Design as a Cultural Education Medium: A Study of Elementary School Student Involvement - Muhammad Naufal Alfitro Sasinov; Rojjer Ranggajaya (Journal of Interdisciplinary Social Sciences and Humanities, 2026)
This study aims to examine batik-based interior design as a cultural education medium to increase the engagement of elementary school students. The background of this study is based on the minimal integration of local cultural values ​​in classrooms, which tend to be functional and lack an educational-cultural dimension. The study used a descriptive qualitative approach with a design thinking method that includes the stages of empathize, define, ideate, prototype, and test. The study was conducted in grades 5–6 of Wangan Elementary School, Boyolali, involving 20 students as participants. The design implementation was realized through the development of interior elements in the form of batik-based accessories that integrate the philosophical values ​​of Parang, Kawung, Mega Mendung motifs, as well as local flora and fauna. The results of the study indicate that the application of batik-based interior design not only enriches the aesthetics of the space but also functions as a cultural education medium that can increase student engagement in the learning process. The integration of cultural values ​​in interior elements encourages students to recognize, understand, and appreciate local cultural heritage in a more contextual manner. This study confirms that interior design has the potential as a strategic medium in connecting educational functions and cultural preservation in elementary education environments